Conceptualizing the e-Learning Assessment Domain using an Ontology Network - Romero, Lucía; Gutiérrez, Milagros; Caliusco, María Laura (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
During the last year, approaches that use ontologies, the backbone of the Semantic Web technologies, for different purposes in the assessment domain of e-Learning have emerged. One of these purposes is the use of ontologies as a mean of providing a structure to guide the automated design of assessments. The most of the approaches that deal with this problem have proposed individual ontologies that model only a part of the assessment domain. The main contribution of this paper is an ontology network, called AONet, that conceptualizes the e-assessment domain with the aim of supporting the semi-automatic generation of it. The main advantage of this network is that it is enriched with rules for considering not only technical aspects of an assessment but also pedagogic.
Keywords: e-assessment; ontology network; e-learning; IJIMAI